1999
DOI: 10.1086/314691
|View full text |Cite
|
Sign up to set email alerts
|

Persistently High Epstein‐Barr Virus (EBV) Loads in Peripheral Blood Lymphocytes from Patients with Chronic Active EBV Infection

Abstract: Chronic active Epstein-Barr virus infection (CAEBV) is a severe illness with unusual EBV activation that persists for years, and its pathogenesis is largely unknown. After the creation of an accurate and reproducible polymerase chain reaction system to quantify EBV DNA, virus loads in peripheral blood lymphocytes (PBL) were determined in 54 children: 15 with CAEBV, 16 with infectious mononucleosis (IM), and 23 healthy children. Children with CAEBV and those with IM had high virus loads. Lower loads were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
3
32
1
1
Order By: Relevance
“…The viral burden of that sample was estimated to be 4,000 genome copies per 10 4 PBMCs, which was similar to values reported for patients with EBV LPD 41 or chronic active EBV infection. 42 The CTLp level of this patient (340 per 10 6 PBMCs) was similar to that of healthy carriers, and the patient did not show symptoms of either EBV disease. Further amplification revealed the viral genome in 3 other samples, with an estimated viral burden of 1-30 copies (Fig.…”
Section: Ebv Ctlp Frequency and Ebv Burdensupporting
confidence: 53%
“…The viral burden of that sample was estimated to be 4,000 genome copies per 10 4 PBMCs, which was similar to values reported for patients with EBV LPD 41 or chronic active EBV infection. 42 The CTLp level of this patient (340 per 10 6 PBMCs) was similar to that of healthy carriers, and the patient did not show symptoms of either EBV disease. Further amplification revealed the viral genome in 3 other samples, with an estimated viral burden of 1-30 copies (Fig.…”
Section: Ebv Ctlp Frequency and Ebv Burdensupporting
confidence: 53%
“…Higher values of rates of infections with these viruses are generally obtained when serum or plasma is used as a sample using serological diagnosis, in comparison with estimation by a PCR method. Maeda et al [1999] measured copy numbers of EBV in PBLs from EBVseropositive and EBV-seronegative healthy individuals in Japan by a PCR method and found that the EBV genome was present in 47% of seropositive donors (n ¼ 19) but not in seronegative healthy donors (n ¼ 4). Horvath et al [2000] presented results of a large-scale epidemiologic analysis by PCR showing that CMV and EBV prevalence ratios in PBLs are 11.5% and 8%, respectively, in a normal adult population (n ¼ 85).…”
Section: Discussionmentioning
confidence: 99%
“…Since EBV may replicate without causing apparent harm, it is important to be able to distinguish asymptomatic infection from impending or established EBV disease. Because of this, quantitative methods for measuring EBV are now widely utilized for the diagnosis, monitoring, and treatment of EBVrelated diseases, particularly in the case of posttransplant lymphoproliferative disorder (1,9). In addition, studies have indicated that preemptive treatment for EBV and reduction in immunosuppressive therapy can reduce the incidence of posttransplant lymphoproliferative disorder in immunocompromised patients (1,7).…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%